Simultaneous quantitative determinations of fluticasone propionate and salmeterol xinafote in diskus inhalers - (:unkn) unknown (Bentham Science Publishers B.V., 2014)
In the present study, two new methods were developed for the quantitative determination of active components of Seretide®, commercially available pharmaceutical preparation in the diskus form. One of these methods was based on derivative spectrophotometry and used a zero-crossing technique. The determinations of fluticasone propionate and salmeterol xinafoate were performed by first order derivatisation at 216.5 nm and second order derivatisation at 250 nm, respectively. The concentration ranges were 5.0-32.5 μg/mL for fluticasone propionate and 2-12 μg/mL for salmeterol xinafoate. The second method developed also included high performance liquid chromatography. In this method, a methanol-water mobile phase mixture (95:5, v/v) and a C18 chromasil column as a stationary phase were used. The wavelength of the diode array UV detector was 260 nm; the flow rate was 1 mL/min. The concentration ranges were 2-16 μg/mL for fluticasone propionate and 1-8 μg/mL for salmeterol  xinafoate. The results for both methods from diskus are in the pharmacopea limits. For the statistical determination of these results, these two methods were compared with t-test for the means and with F-test for the standard deviations. © 2014 Bentham Science Publishers.
Keywords: Derivative spectrophotometry; Fluticasone propionate; HPLC; Quantitative determination; Salmeterol xinafoate